Hashemite Kingdom of Jordan Promoting Poverty Reduction and Shared Prosperity : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2016)
Jordan is an upper middle income country which has proven remarkably resilient despite decades of turmoil in its neighborhood. Even with economic stability in the face of massive shocks, the Jordanian government - reflecting the views of the population - has made clear the need for improvement in the current growth trajectory. Public dissatisfaction coalesced around a perception, which the government acknowledges, that previous reform efforts had struggled with implementation, while discretionary decisions and unequal opportunities remain entrenched. In response, the government is moving to the implementation phase of its Jordan 2025 strategic blueprint, a new ten-year strategy formally launched in May 2015. The Bank’s systematic country diagnostic (SCD) is therefore unfolding at a critical inflection point for the government. Given existing reform momentum around the energy sector and investment, the substantive engagement of the Bank Group and other development partners, the SCD will seek added value by providing an integrative and concise perspective on what Jordan can do to better meet the expectations of its citizens. As a multi-sector evidence-based diagnostic, the SCD relies upon consistent and integrated analysis of data from various sources.